An English debate league competition among lower form students: an experiential learning activity - Othman, Moomala; Mohamad, Faizah; Amiri, Farzaneh (David Publishing Company, 2013)
This paper presents a study of an experiential learning debate program held among second language learners of a Malaysian boarding school. It was a co-curricular activity carried by the ELS (English language society) and the EDC (English debate club). The English panel felt that not everyone would have the chance to speak or voice their opinion in a 40-minute English lesson. Hence, the rational to hold the debate tournament as this would create a real context for students to use English language. The British parliamentary debate was adopted. Thirty-two ELS members were briefed to run the tournament whilst 24 English debate members were trained to adjudicate. Two hundred and forty students (120 form one and 120 form two students) were grouped in pairs as debaters according to their sports house system. The debate lasted for three months and quantitative and qualitative data was drawn. A survey of participants’ perception undertaken revealed that students felt they had improved their speaking and listening skills. They suggested that after each debate, the adjudicators should discuss the motion and inform them of their weaknesses. Later, data drawn was used to explain how debate helped students to develop their speaking ability.